State regulation of the mortgage market as a factor in the organization of housing market financing (Journal of Economic Research & Business Administration, 2019)
Providing citizens with affordable housing is one of the priority tasks of the state. Mortgage lending is indicated as one of the main instruments for financing the housing market. The ongoing national project, Housing and Urban Environment, also puts forward a mortgage loan as the main source. The aim of the study is to identify the main milestones in the development of mortgage lending and determine the role of the state in this process, as well as the formation of measures that will more likely provide conditions for the availability of mortgage loans for the population. The national project indicates the need for an electronic mortgage market, but does not present mechanisms to achieve this.The methodological basis of the study was the work of Russian and foreign scientists who present various approaches to the development of mortgage lending, but no general system is presented. The practical significance of the presented work lies in the fact that the author suggests using crowdfunding, which will create the prerequisites for organizing a fully functioning electronic mortgage market, the need for which is indicated in the national project. In addition, the value of the study is to justify the need for the development of funded systems, which can become an element of the electronic platform, and can take into account the funding sources provided in Russia for various categories of citizens.